Implementasi Model CRI dengan Strategi Tugas dan Paksa untuk Mengurangi Miskonsepsi Matematika - Ichwan Maulana; Leonard Leonard (Universitas Indraprasta PGRI Jakarta, 2022)
The purpose of this study is to determine the decrease in students' mathematical misunderstandings through the CRI learning model with a constructivism approach modified with task and forced learning strategies in students of SMP PGRI Jatiuwung and SMP Muhammadyah 5. The research method used was an experimental method, with a Pretest-Posttest Control Group Design research design. The population in this study was all students of SMP PGRI Jatiuwung and SMP Muhammadyah 5, while the affordable population was students of SMP PGRI Jatiuwung and SMP Muhammadyah 5 years in 2021/2022. The sample in this study was 60 eighth graders. Before the analysis, the first data were tested for normality using the Lilliefors test and tested for homogeneity using the Fisher test. Based on hypothesis testing, thitung = -0.893 and ttabel = 2.002 at a significance level of 5% with a degree of freedom (dk = 58) which means (-0.883) < (2.002). It can be concluded that the decline in student misunderstandings in the experimental group is better than in the control group. This suggests that CRI learning models with a constructivism approach modified with task and forced learning strategies can reduce students' mathematical misunderstandings.